2018
DOI: 10.20944/preprints201806.0202.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Feasibility of Using Marble Cutting Waste in a Sustainable Building Clay Industry

Abstract: This study evaluates the feasibility of stabilizing clay bricks with marble cutting waste (MCW). This waste currently discarded in huge quantities as a sludge resulted from sawing the marble blocks to slabs, grinding and polishing of marble processes to the landfills located around the marble processing factories located in the Shaq El-Thoban industrial zone, Cairo governorate, Egypt causing negative impacts on the environment, health and sustainable development. Experimental investigations were carried out to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…These reactions can bring the formation of cementitious products, such as calcium-silicate-hydrates (C-S-H), calcium-aluminate-hydrates (C-A-H), and calcium-aluminium-silicate-hydrates (C-A-S-H) [24]. Previous works reported the formation of cementing and poorly crystalline gels when calcium carbonate with lime was added to clays [36].…”
Section: Additivementioning
confidence: 99%
“…These reactions can bring the formation of cementitious products, such as calcium-silicate-hydrates (C-S-H), calcium-aluminate-hydrates (C-A-H), and calcium-aluminium-silicate-hydrates (C-A-S-H) [24]. Previous works reported the formation of cementing and poorly crystalline gels when calcium carbonate with lime was added to clays [36].…”
Section: Additivementioning
confidence: 99%
“…The development of unfired claybased construction products with comparable or better performance than fired products significantly reduces CO2 emissions, reduces consumption of energy that in turn leads to cheaper products with reduced environmental impact. A brief summary of key experimental research work on this clay processing technique can be found in Table 1. El-Mahllawy et al [36] investigated the effectiveness of combining Kafr Homied clay (KHC), Marble Cutting Waste (MCW), hydrated lime (HL) and Portland cement (PC) in the production of sustainable unfired clay brick. The results indicated that the water absorption decreased while the bulk density and compressive strength increased with extended curing time and increase of the MCW content in the presence of HL.…”
Section: Production Of Clay-based Construction Materials Through Blenmentioning
confidence: 99%
“…According to the reviewed studies and amongst the variety of stabilizers utilised, cement and lime have been the most popular stabilizers in the production of stabilised clay-based construction materials. Cement and/or lime were used either alone [37][38][39][42][43][44], in combination with each other [35,36] or in combination with other stabilisers such as GGBS or PFA [45][46][47]. However, two of the reviewed studies were used different stabilisers such as calcium carbide residue with rice husk ash [40] and magnesium oxide rich kiln dust [41].…”
Section: Critical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations